Comparação de técnicas de extração e caracterização de ácidos naftênicos em águas produzidas - Vieira, Michel Moreira de Freitas (2022)
In the first part of the work, for the purpose of studying the extraction efficiency of NAs in Brazilian PWs, some SPE methodologies were studied for these analytes, established in the literature, in order to perform the comparison and determination of the best methodologies, in order to optimize and adapt them to the analytes of the Brazilian scenario. The stationary phases studied in this first part were: C18, ENV, ENV+, Strata-X and HLB. We proceeded with the extractions by fully replicating the parameters as presented in the literature, in order to be able to compare the solid phase extraction methodologies employed to the same matrix. The analyses were performed on the Q-Exactive Orbitrap ultra-high resolution mass spectrometer, using the electrospray ionization (ESI) source in negative mode. Data processing was performed with Composer and Thanus software. The results obtained indicate that the methodologies of group III, with the solid phases ENV and HLB, showed the highest number of AN species extracted with the three solvents used, hexane (HEX), dichloromethane (DCM) and isopropanol (IPA). The results obtained indicate that the solvent DCM extracted in higher concentrations species with a DBE value of 1, and the solvent methanol extracted in higher concentrations species with a DBE value of 2. Moreover, the solvent hexane presented species with a DBE value of 2 in high concentrations, indicating that these species are eluted by this solvent with greater efficiency. Finally, tests with methodologies using ENV, C18, APS, Strata-X and HLB solid phases were performed in order to determine the optimum solvent volume and optimum sample pH for efficient extraction. The results presented indicate that pH 2 showed the highest recovery results for acidic species. Also, the extractions eluted with 20 mL of dichloromethane, divided into two fractions provided better results in terms of the number of formulas assigned. Another point of note is the fact that acid species were eluted by water during the washing step for the removal of salts from the PW sample, making it necessary to remove this step from the extraction methodologies